Bereavement support effectiveness for parents of infants and children: a systematic review. Issue Volume 12:Issue e5(2022) (3rd October 2019) - Ainscough, Tom; Fraser, Lorna; Taylor, Joanna; Beresford, Bryony; Booth, Alison
Abstract : Objectives: This systematic review aims to assess the effectiveness of bereavement support interventions (BSIs) for parents of an infant or a child who has died from a medical condition or in unforeseen circumstances. Methods: A systematic search of MEDLINE, PsycINFO, Embase and CINAHL (1980 to January 2018) was performed to identify studies investigating BSIs for the parents of children who died between the ages of 24 weeks gestation and 30 years. Due to significant clinical and methodological heterogeneity between studies, a narrative synthesis was performed. Results: The database searches returned 24 550 records, with a further 6 identified through other sources. Of these, eight studies, reported in nine papers, met the inclusion criteria. Most studies were conducted in the USA (n=5) and in perinatal/neonatal deaths (n=6). Five of the included studies were randomised controlled trials and three were non-randomised comparative studies. Interventions were delivered to groups, individuals or families. Outcomes of interest were grief, mental health, physical health and 'others'. There were major concerns over the quality of study methods and reporting. Only three of the nine studies reported a significant difference between experimental and control arm participants in any outcomes, despite a total of 23 outcomes being measured. Conclusions: Poor methodology and reporting of the few studies which have assessed BSIs for parents limit any conclusions on their effectiveness. Agreement on core outcomes and more robust study methodology are required in this neglected area of research.